Johann Adolph Grosssteinbeck - unknown:::Creator::::::::::::
Johann Adolph Grosssteinbeck,1832-1913, John Steinbeck's grandfather. He later shortened his name to Steinbeck. He was a carpenter who migrated from Elberfeld in western Germany to the Jaffa area in the Ottoman Empire, now Israel, in 1850. He came with his brother (Friedrich), sister (Maria Katharina), her husband (Gustav Thiel), and two other families. They emigrated in an attempt to teach local Jews agrarian practices and attract Jews in the diaspora back to Palestine. He married Almira Ann Dickson (1828-1923) while there. After his brother was killed in Palestine, he emigrated to Florida, fought for the Confederacy, moved to Massachusetts, where the Dicksons lived, and then moved on to California. Digital copy only. No hard copy.